Drug use during pregnancy - Sandoval Paredes, José (2018)
There is plenty of information about drug safety during pregnancy, but there is little scientific evidence on this topic. Due to ethical reasons, very scarce clinical assays have been conducted and published. This situation has resulted in the exaggeration of drug risk during pregnancy, thus limiting its reasonable use for chronic diseases in pregnant women. At the other extreme, it has resulted in the careless prescription of drugs not acknowledging the real risk involved in administering them in the inappropriate dose and moment. This review article describes how physiological changes during pregnancy modify significantly the pharmacokinetics of drugs. The real potential risk of drug-induced teratogenesis and the specific criteria for considering them an etiological factor are evaluated. The U.S. Food and Drug Administration (FDA) pregnancy categories' criteria, limitations, and limited current validity are discussed, as well as its proposal of new regulations on drug labeling, considering clinical evaluations, unnoticed exposure, and risks. The risks associated with the most frequently used drugs for the most common diseases during pregnancy are described. The correct way to tell the patient exposed to suspected teratogens is discussed, in order to avoid affecting risk perception. It should be considered that the administration of the most frequently prescribed drugs is relatively safe during pregnancy. Nevertheless, only those strictly necessary must be prescribed, their consumption must be limited during the first trimester, those proven safety must be preferred, the minimum effective dose during the shortest time possible must be used, the administration of several drugs must be avoided, and side effects and complications must be monitored.